2015
DOI: 10.1007/s10902-014-9611-7
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being and Its Association with Subjective Health Status, Age, Sex, Region, and Socio-economic Characteristics in a Chinese Population Study

Abstract: This study analyse how subjective well-being (SWB) in a Chinese population varies with subjective health status, age, sex, region and socio-economic characteristics. In the Household Health Survey 2010, face-to-face interviews were carried out in urban and rural counties in eastern, middle and western areas of China (n = 8,000, aged 15-102 years). To measure subjective health status, a global self-rated health question, the EQ-5D descriptive system, and a visual analogue scale of health status was included. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(73 citation statements)
references
References 47 publications
8
57
1
1
Order By: Relevance
“…Subjective personal health is one variable that is rarely used (an exception is the study by Sun et al 2015), mainly because a good quality version of this variable is missing in the data. On the other hand, it is not clear whether it should be included.…”
Section: Model Implementation Of This Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Subjective personal health is one variable that is rarely used (an exception is the study by Sun et al 2015), mainly because a good quality version of this variable is missing in the data. On the other hand, it is not clear whether it should be included.…”
Section: Model Implementation Of This Studymentioning
confidence: 99%
“…The earlier studies have used both multinational and national surveys but more often national such as Chinese Population Study (Sun et al 2015), German Socio-economic panel (e.g., van Praag et al 2003). Frijters and Beatton (2012) used the three national surveys in one study, that is, the American General Social Survey, the British Household Panel and the Hilda Survey (Survey (Household, Income and Labour Dynamics in Australia).…”
Section: Data and Data Handlingmentioning
confidence: 99%
See 2 more Smart Citations
“…Easterlin (2003) also notes increases in life satisfaction among those who married in the first decade of adulthood. However, numerous studies have suggested that married people are more satisfied with life than the never-married or previously married people (Heliwell, 2003;Strine, Chapman, Balluz, Moriarty, & Mokdad, 2008;Mousavi, Shiani, Mohammadi, Sadjadi, Tabatabaee, & Assari, 2011;Sun, Chen, Johannesson, Kind, & Burström, 2016).…”
Section: International Journal Of Social Science Researchmentioning
confidence: 99%